The Optimizing Differentiated Learning in Elementary Schools: An Experimental Study of the CIRC Method for Children with Reading Difficulties - Ranti Novianti; Melor MD Yunus; Sisca Sriyanti; Yoga Budhi Santoso; Ica Purnamasari; Salma Nadiyah; Ana Fatimatuzzahra (Universitas Pendidikan Ganesha, 2025)
Reading difficulties, especially among students with dyslexia, pose a serious obstacle to the development of academic and social competencies. This study examines the effectiveness of the Cooperative Integrated Reading and Composition (CIRC) method in improving the reading comprehension of students with reading difficulties in a differentiated learning context. This study uses a quantitative approach with a one-group pretest-posttest pre-experimental design. The sample consisted of 11 fourth and fifth-grade students identified as having dyslexia through teacher assessments and initial observations. Data were collected using reading comprehension tests at pretest and posttest, as well as observations of the intervention process. Data analysis was conducted using the Wilcoxon test to determine statistical differences in scores. The results showed an increase in the average score from 15.2 to 25 after the implementation of the CIRC method. The Asymp. Sig. (2-tailed) of 0.003 (<0.05) indicates a statistically significant improvement. The conclusion of this study confirms that CIRC can create a collaborative and inclusive learning environment that contributes to increased student engagement and confidence in reading. Implications suggest that CIRC is recommended as an effective differentiated learning strategy for students with reading difficulties in elementary school.